Does Politicization Matter? Small States in East-Central Europe and the Brexit Negotiations. Issue 1 (February 2021) - Csehi, Robert I.; Kaniok, Petr
The integration process is increasingly politicized across the member states of the European Union (EU). While this phenomenon has been analyzed from many perspectives, this article aims to look at a so far neglected aspect—how increased levels of politicization of the EU might have impacted on the role small states play in the EU decision-making process. Using the case of Brexit negotiations, the article starts from the hypothesis that higher levels of politicization could increase the influencing capacity of smaller states. As national sovereignty concerns may become more relevant due to politicization, it can be expected that small states become more active in EU-level negotiations, especially in cases where the future of the integration is also at stake. However, looking at the cases of Czechia, Hungary, Slovakia, and Slovenia, the article concludes that the behavior of these countries is still determined by their small-state character. Interestingly, different levels of EU politicization did not determine their bargaining strategies in Brexit negotiations. Consequently, while we see a slight variation in the level of engagement, the article argues that the influencing capacity of the member states under scrutiny was mainly driven by their small state characteristics.